Factors Driving Customer Repurchase Intention - A Meta Analysis - Kavitha, K.; Celina, A.; Priya, S. (Indian Journal of Marketing, 2025)
Purpose : Repurchase intention, a key metric in marketing, reflects a customer’s likelihood of buying again from a company. This meta-analysis examined factors influencing repurchase intention across various industries. By integrating findings from multiple studies from different databases, this meta-analysis offered insights into the relative importance of various factors and their nuanced interactions in shaping consumers’ repurchase intention. Design/Methodology/Approach : Analysis of 137 effect sizes and 28,502 aggregate samples from 63 studies conducted between 2014 and 2024 was carried out. Key constructs analyzed included customer satisfaction, perceived value, brand preference, and service quality on repurchase intention. The meta-analysis for the study was conducted using Jamovi Software. Findings : The research explored the most influential factors, highlighting the relative importance of the different constructs and their interactions. The analysis identified the key determinants that impact the consumer’s likelihood to repurchase. Practical Implications : The implications of these findings for theory development, managerial practice, and future research directions were discussed, highlighting avenues for enhancing consumer loyalty and strategic marketing efforts. Originality/Value : This meta-analysis contributes to a deeper understanding of the complex dynamics underlying consumers’ repurchase intention, providing valuable insights for businesses seeking to optimize their marketing strategies and cultivate enduring relationships with their customers.